Importance of genetic counseling in preimplantation genetic testing for aneuploidies (PGT-A) - Sessarego Tabja, Silvana (2019)
The development of new genomic technologies has strengthened the influence of genetics in all medical specialties; reproductive medicine is no exception. The introduction of new genetic tests to daily clinical practice, together with the complexity of genetic information and its potential psychological burden, make specialized genetic counseling essential. Preimplantation genetic testing for aneuploidies (PGT-A) has become an almost routine procedure in assisted reproduction treatments. Nevertheless, in Peru, patients usually receive none or inadequate corresponding genetic counseling, which hinders informed decision-making.